Current status of intestinal transplantation in East Asia. Issue 2 (April 2020) - Hibi, Taizo; Chen, Yun; Kim, Ji-il; Lee, Myung Duk; Matsuura, Toshiharu; Ueno, Takehisa
Abstract : Purpose of review: Intestinal transplantation (ITx) activity remains low in East Asia. We conducted a multinational, retrospective study on patients who underwent ITx in Korea, Taiwan, and Japan, to provide an overview and to foresee future developments and collaborations in this region. Recent findings: Total 71 ITx were performed in 67 patients. Living donor ITx was most commonly conducted in Japan ( n = 13). Despite the low caseload, all three countries demonstrated acceptable patient survival rates of approximately 70% at 5 years. Over 70% of recipients with a functioning graft were free from total parenteral nutrition. Summary: There is an urgent need to establish a nationwide and multinational registry of ITx recipients and patients with intestinal failure in East Asia. An efficient referral system to specialized intestinal rehabilitation and ITx centers and a multidisciplinary team approach is also warranted to provide state-of-the-art treatment for patients desperately waiting for a chance to survive.